PENGARUH PAKET MOBILISASI TERHADAP STATUS FUNGSIONAL PASIEN STROKE - Mulyati, Leli (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Patients who got stroke should be took rehabilitation program. Furthermore, theability for life reorganization to reach optimal health level. Especially for neurologic function afterstroke attacked, for preventing disability and gain quality of their life. Nursing intervention atacute phase is important to establish for supporting reorganization of patient functions. One ofthat interventions is training the patient to do structured early mobilization. Aims of this study isto identified influenced of early mobilization against functional state of patient who got stroke.This was a descriptive study, a quasi experimental study. There were two group of study, dividedto intervention group and control group. The samples of this study were stroke patient at StrokeUnit in M.Yunus Hospital of Bengkulu with total amount 64 respondents, wich picked by consecutivesampling. Measurement of functional status using the NIHSS score, which was measuredon admission to hospital and the time the patientat discharge. The results showed an averageNIHSS scores of stroke patients on admission is 11.56, SD 5.58 (moderate stroke). Meanwhile,the average NIHSS score when out of the hospital was 8.89, SD 7.6 (moderatestroke).Mean score for improved NIHSS patient who done structured training of mobilization is4.87, SD 4.42 and score for patient who didn’t do training is 0.313, SD 4.46. After statistic testshowed that p value = 0.000 < alpha. It’s mean that there were significantly differences betweenNIHSS score for the patient who got structured early mobilization and who didn’t. Structuredearly mobilization must be establish, and it’s need collaboration from patient and family.